Controlling chaos through growth rate adjustment - Weihong Huang (Discrete Dynamics in Nature and Society)
An extremely fast growth-rate controlling mechanism has been developed to stabilize a discrete system. Theoretical analysis and computer simulations have been provided to show the effectiveness and efficiency of this new mechanism in practice.